IJCM_218A: Association between school bag weight and trunk strength among children in Mangalore - Soy Elsa Maria; Rekha T; Unnikrishnan Bhaskaran; Mithra Prasanna; Kumar Nithin; Joshua Abraham M; Mohamed Fida; Sahni Anjali; Venkatachalam Vedant; Arora Gaurav; Gannu Abhishek; Holla Ramesh (Wolters Kluwer Medknow Publications, 2024)
Background: School bags serve as a practical means for students to transport essential academic materials and personal items, including food. The significance of school bag weight has garnered increased attention in recent years due to its potential impact on the musculoskeletal health of school children. Excessive school bag weight has been identified as a significant contributor to various health issues, ranging from neck pain and shoulder discomfort to headaches, general fatigue, decreased muscle strength, and, notably, back injuries among children. Methods: The study involved 178 school children in Mangalore, ranging from 10-15 years, for a period of 23 days. School bag weights were measured using calibrated scales, and trunk strength was assessed using a hand held dynamometer. Statistical analysis, including Chi-square test, student's 't' test and Karl Pearson correlation test were employed to identify any significant relationships between these variables. Results: Preliminary findings revealed a positive correlation between school bag weight and trunk strength among the participants. Results indicated that a considerable proportion (83.1%) of students were burdened with an excessive load of bags. The evaluated muscular strength was discovered to be diminished in these individuals, and they experienced symptoms that were interconnected, highlighting the potential impact of school bag weight on the musculoskeletal health of children in Mangalore. Conclusion: These findings advocate measures to alleviate the burden on children's musculoskeletal health. Further research and interventions are warranted to promote a balanced and healthy school environment for the well-being of the younger generation.